Relationships Between Generational Handover Protocols, Knowledge Transfer Behavior, and Key Organizational Outcomes - Elene Igoa-Iraola; Fernando Díez; José Miguel Román (Systems)
(1) Background: This paper examines the relationships between generational handover protocols, knowledge transfer behavior, and key organizational outcomes. (2) Methods: A quantitative design was applied, using non-parametric tests and partial least squares structural equation modeling (PLS-SEM) on survey data from 168 employees in companies located in the Basque Country. (3) Results: The presence of formal knowledge transfer protocols and generational handover processes was significantly associated with greater employee knowledge-tranfer behaviors. These behaviors, in turn, had significant positive effects on organizational innovation and job performance. Although moderate correlations were observed with strategy, performance, and competitive advantage, the structural model did not confirm direct relationships. (4) Conclusions: Despite their strategic importance, many organizations still lack formalized mechanisms for knowledge preservation. This study offers a framework for understanding the impact of structured knowledge transfer practices on organizational performance and suggests avenues for future research in knowledge continuity and succession planning.